Relationship between Emergency Department Triage Data and 24- and 48- Hour Mortality in an Academic Teaching Hospital - Aviesena Zairinal, Ramdinal; Amanah, Salma Rizqi (Writing Center IMERI FMUI, 2025)
Introduction: Triage data plays an essential role in the initial assessment and prioritization of emergency patients. However, the association between triage parameters and short- term mortality remains underexplored. Evaluating 24-hour and 48-hour mortality may serve as an indicator of the effectiveness of triage and early resuscitation efforts. Objectives: To determine the relationship between emergency department triage parameters and short-term mortality (24-hour and 48-hour) among patients treated at an academic teaching hospital. Methods: A retrospective cohort study was conducted on all patients admitted to the emergency department from January to February 2024. Demographic and clinical data obtained during triage were analyzed. Bivariate and multivariate binary logistic regression analyses were performed to identify factors associated with 24-hour and 48-hour mortality. Results: A total of 1,976 patients were included. The 24-hour and 48-hour mortality rates were 1% and 5%, respectively. Significant predictors of 24-hour mortality were triage category (OR = 4.42; 95% CI 1.93–10.09), respiratory rate (OR = 1.09; 95% CI 1.02–1.16). Predictors of 48-hour mortality included age (OR = 1.02; 95% CI 1.008–1.036), triage category (OR = 3.23; 95% CI 2.23–4.67), respiratory rate (OR = 1.08; 95% CI 1.03–1.13), systolic blood pressure (OR = 0.98; 95% CI 0.97–0.99), and mental status (OR = 3.58; 95% CI 2.11–6.07). Conclusion: Several routinely collected data during initial admission to the emergency unit are independently associated with both 24-hour & 48-hour mortality. These results highlight that triage data can serve as meaningful predictors of early mortality and may support rapid risk stratification, resource allocation, and operational decision-making in the Emergency Department.